The photographer's eye composition and design for better digital photos - Freeman, Michael (Boston Focal Press, 2007)
Presents instructions on traditional photographic composition and addresses the new techniques of digital photography that allow the image to be edited, manipulated, or montaged to produce a radically different final result.
Includes bibliographical references and index.
Keywords: Photography -- Digital techniques